The understanding of the concept of business in terms of the concepts of GAME/SPORT with the example of business English idioms - Milošević Ivan (Turističko Poslovanje, 2016)
This paper focuses on the potential understanding of the concept of BUSINESS in terms of the concepts of GAME and SPORT with the examples of Business English idioms (idiomatic expressions). Namely, in the light of the cognitive linguistics, meaning is considered to be not only a linguistic phenomenon, but a conceptual phenomenon as well. Such vantage point enables a lexico-semantic interpretation of linguistic units from a conceptual perspective, which includes the forming of correspondences between two concepts, with one concept being understood in terms of the other. The analysis includes 24 Business English idioms which stem from the conceptual domain of GAME/SPORT and is aimed at establishing the conceptual mapping (primarily via a cognitive mechanism known as the conceptual metaphor) between the above stated source and the target domains, which prove a potential understanding of the concept of BUSINESS on the basis of the concepts of SPORT and GAME.